2020
DOI: 10.1063/5.0006137
|View full text |Cite
|
Sign up to set email alerts
|

Phase control of α- and κ-Ga2O3 epitaxial growth on LiNbO3 and LiTaO3 substrates using α-Fe2O3 buffer layers

Abstract: LiNbO3 and LiTaO3 substrates are used in wide-bandwidth applications such as surface acoustic wave filter and show structural similarity to α-Ga2O3. In this study, we demonstrated the phase control of Ga2O3 epitaxial thin films, grown by mist chemical vapor deposition, on the (0001) planes of LiNbO3 and LiTaO3 substrates using α-Fe2O3 buffer layers. κ-Ga2O3 thin films were grown epitaxially on bare LiNbO3 and LiTaO3 substrates. Conversely, the insertion of the α-Fe2O3 buffer layer led to the preferential growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…However, research on κ-Ga 2 O 3 -based HEMT applications is still in its early stages and mainly concerned with thin film deposition and growth. The growth methods of κ-Ga 2 O 3 that have been reported to date include hydride vapor-phase epitaxy, , metal–organic chemical vapor deposition (MOCVD), mist CVD, molecular beam epitaxy (MBE), , and pulsed laser deposition (PLD). Since κ-Ga 2 O 3 is a metastable phase, its phase-controlling techniques are essential for thin film growth. In MBE and PLD, which are categorized as physical vapor deposition methods, the phase control of κ-Ga 2 O 3 requires the assistance of Sn or In .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research on κ-Ga 2 O 3 -based HEMT applications is still in its early stages and mainly concerned with thin film deposition and growth. The growth methods of κ-Ga 2 O 3 that have been reported to date include hydride vapor-phase epitaxy, , metal–organic chemical vapor deposition (MOCVD), mist CVD, molecular beam epitaxy (MBE), , and pulsed laser deposition (PLD). Since κ-Ga 2 O 3 is a metastable phase, its phase-controlling techniques are essential for thin film growth. In MBE and PLD, which are categorized as physical vapor deposition methods, the phase control of κ-Ga 2 O 3 requires the assistance of Sn or In .…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that various substrates and templates can be used for the growth of κ-Ga 2 O 3 . These substrates include the following: (0001) α-Al 2 O 3, ,,, LiTaO 3, LiNbO 3 (rhombohedral), (0001) GaN, AlN, ,, 6H-SiC (hexagonal), (111) yttria-stabilized zirconia (YSZ), , MgO, , STO, NiO, ITO (cubic), (201) β-Ga 2 O 3 , (monoclinic), and (100) SnO 2 (tetragonal). It has been found that κ-Ga 2 O 3 grew epitaxially on these substrates.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, because it is difficult to grow the metastable κ phase as a single bulk crystal, it is important to select a suitable substrate for heteroepitaxial growth. Various substrates, such as (0001) α-Al 2 O 3 , [21][22][23][24][25][26] (0001) LiTaO 3 , 27 (0001) LiNbO 3 , 27 (0001) GaN, 21,25,28,29 (0001) AlN, 25,28,30,31 (0001) ZnO, 32 (111) YSZ, 33 (111) MgO, 33,34 (111) STO, 29,34 (111) NiO, 35 (100) SnO 2 , 18 and (−201) β-Ga 2 O 3 , 25,28 are used for the growth of κ-Ga 2 O 3 . It is noteworthy that the metastable κ-Ga 2 O 3 phase can be grown on β-Ga 2 O 3 substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the early growth studies had reported the κ-phase (space group: P na 2 1 ) as the hexagonal ε-phase (space group: P6 3 mc). Recently, it was found that the ε-phase actually consists of 120°-rotated nanoscale κ-phase domains. , In an effort to improve the structural quality, the impacts of different substrates (sapphire, GaN, AlN, SrTiO 3 , yttria-stabilized ZrO 2 , and MgO) on the epitaxial growth have been investigated. In addition to the crystal quality, the thermal stability of this metastable phase needs to be enhanced for the long-term reliability of a device operating under an extreme environment (i.e., high temperature and high pressure). Recently, several research groups reported that the introduction of elemental Sn during a Ga 2 O 3 growth could facilitate the preferential growth of the κ-phase. , So far, this phenomenon has been observed with physical vapor techniques such as pulsed laser deposition (PLD) and molecular beam epitaxy (MBE) but not with chemical vapor techniques to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%